Is Genuine Satisficing Rational? - Henden, Edmund (Ethical theory and moral practice, 2007)
There have been different interpretations of satisficing rationality. A common view is that it is sometimes rationally permitted to choose an option one judges is good enough even when one does not know that it is the best option. But there is available a more radical view of satisficing. On this view, it is rationally permitted to choose an option one judges is good enough even when a better option is known to be available. In this paper I distinguish between two possible interpretations of ‘genuine’ satisficing, a de re and a de dicto interpretation. I then argue that while de re genuine satisficing is always irrational, de dicto genuine satisficing might be rationally permissible. In fact, de dicto genuine satisficing does not appear to be covered by existing accounts of satisficing behaviour.